2015
DOI: 10.5505/tjtes.2015.91650
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Evaluation of Pneumothorax by Imaging Methods in Patients Presenting to Emergency Department for Blunt Thoracic Trauma

Abstract: BACKGROUND: Pneumothorax (PNX) is the collection of air between parietal and visceral pleura, and collapsed lung develops as a complication of the trapped air. PNX is likely to develop spontaneously in people with risk factors. However, it is mostly seen with blunt or penetrating trauma. Diagnosis is generally confirmed by chest radiography [posteroanterior chest radiography (PACR)]. Chest ultrasound (US) is also a promising technique for the detection of PNX in trauma patients. There is not much literature on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…(10) In a single-blind prospective clinical study, chest ultrasonography was more reliable for early bedside diagnosis of pneumothorax compared with supine chest radiography. (11) Langdrof et al have shown, in a multicentre prospective study, that 71% of chest injuries would be missed if chest radiography was done without chest CT for occult injuries and that 14% of these occult injuries would need major interventions, including chest tube insertion for haemothorax or pneumothorax, mechanical ventilation or surgery. (2) CT is more sensitive and specific when compared to chest radiography and significantly reduces the time for patient management in emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“…(10) In a single-blind prospective clinical study, chest ultrasonography was more reliable for early bedside diagnosis of pneumothorax compared with supine chest radiography. (11) Langdrof et al have shown, in a multicentre prospective study, that 71% of chest injuries would be missed if chest radiography was done without chest CT for occult injuries and that 14% of these occult injuries would need major interventions, including chest tube insertion for haemothorax or pneumothorax, mechanical ventilation or surgery. (2) CT is more sensitive and specific when compared to chest radiography and significantly reduces the time for patient management in emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers described cases with clinically significant pneumothorax who were not diagnosed by chest ultrasonography due to the uneven distribution of pneumothorax in the pleural cavity with pulmonary adhesions to the chest wall with or without lung contusion. Moreover, "double lung point sign" as reported, may under or overestimate the PTX size by ultrasonography [4,7,19]. The extent of PTX was estimated by Blaivas et al assessing the pleural sliding in several intercostal spaces and identified fair correlation with CT scan findings.…”
Section: Analysis Of False-negative Results and Other Shortcomings Ofmentioning
confidence: 99%
“…They also evaluated pleural sliding by standard scan areas of “Power Doppler” to detect the fine pleural shimmering that may be difficult to detect due to resolution limitations [ 20 , 21 ]. Some suggested differential diagnoses of dyspnea account for the most false-positive pneumothoraces in intensive care units including lung cancer, significant pulmonary infiltration or contusion, pleural or pulmonary adhesions and thoracic surgery, and in other settings such as achalasia [ 7 , 22 ], many of which are grouped in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations